Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 215820 by Jubr last updated on 18/Jan/25

Commented by A5T last updated on 18/Jan/25

This is not generally true, it fails when c=0.

Thisisnotgenerallytrue,itfailswhenc=0.

Answered by Rasheed.Sindhi last updated on 18/Jan/25

ax^2 +bx+c=0  x=((−b±(√(b^2 −4ac)) )/(2a))×((−b∓(√(b^2 −4ac)))/(−b∓(√(b^2 −4ac))))  x=((b^2 −(b^2 −4ac))/(2a(−b∓(√(b^2 −4ac)))))    =((4ac)/(2a(−b∓(√(b^2 −4ac)))))    =((2c)/(−b∓(√(b^2 −4ac))))

ax2+bx+c=0x=b±b24ac2a×bb24acbb24acx=b2(b24ac)2a(bb24ac)=4ac2a(bb24ac)=2cbb24ac

Commented by Jubr last updated on 19/Jan/25

Thanks sir.

Thankssir.

Answered by A5T last updated on 18/Jan/25

ax^2 +bx+c=0  x≠0⇒c((1/x))^2 +b((1/x))+a=0  ⇒(1/x)=((−b+_− (√(b^2 −4ca)))/(2c))(c≠0)  ⇒x=((2c)/(−b+_− (√(b^2 −4ac)))) when c≠0 and x≠0

ax2+bx+c=0x0c(1x)2+b(1x)+a=01x=b+b24ca2c(c0)x=2cb+b24acwhenc0andx0

Commented by Jubr last updated on 19/Jan/25

Thanks sir

Thankssir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com